2016
DOI: 10.1111/ctr.12736
|View full text |Cite
|
Sign up to set email alerts
|

Routine prophylaxis with proton pump inhibitors and post‐transplant complications in kidney transplant recipients undergoing early corticosteroid withdrawal

Abstract: Surgical stress, corticosteroids, and mycophenolate may contribute to gastrointestinal ulcers/bleeding after kidney transplantation. Prophylactic acid suppression with H2RAs or PPIs is often utilized after transplantation, although unclear if truly indicated after early corticosteroid withdrawal (CSWD). PPIs have been associated with increased risks of Clostridium difficile infection (CDI), pneumonia, and acute rejection. This retrospective cohort study investigated benefits and risks of prolonged PPI use foll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 41 publications
0
17
0
Order By: Relevance
“…However, the clinical significance of this drug interaction in kidney transplant recipients is unknown. Several studies[20,21] have shown a possible increased risk of acute rejection with PPI exposure whereas others have not[22-24].…”
Section: Introductionmentioning
confidence: 99%
“…However, the clinical significance of this drug interaction in kidney transplant recipients is unknown. Several studies[20,21] have shown a possible increased risk of acute rejection with PPI exposure whereas others have not[22-24].…”
Section: Introductionmentioning
confidence: 99%
“…The precise mechanisms resulting in the reduction in prevalence and risk of H. pylori among people with adult kidney transplant are still unclear. However, proton pump inhibitors are commonly prescribed among kidney transplant recipients . Also, kidney transplant recipients often received antibiotics prophylaxis (eg, for prevention of urinary tract infection) .…”
Section: Discussionmentioning
confidence: 99%
“…Chronic use of PPIs has tremendously increased over the past decade, and studies estimate that in both primary and hospital care 30% to 65% of patients that chronically use PPIs are using it for an inappropriate indication [57][58][59][60][61], including, e.g., corticosteroid therapy without concomitant nonsteroidal anti-inflammatory drug (NSAID) use [61,62]. Inappropriate use of PPIs may be frequent in KTRs, since PPIs are commonly prescribed to prevent gastrointestinal complaints and complications of immunosuppressive medication, particularly of corticosteroid therapy [63]. According to the Food and Drug Administration (FDA) guidelines, PPI use is not routinely indicated in this situation [64,65].…”
Section: Plos Medicinementioning
confidence: 99%